The Analysis of Things and Signs Concepts by St. Augustine Found in Khotbah di Atas Bukit Novel (Semiotic Study) - Maulida, Delara Siti (Foremost Journal, 2022)
In the light to St. Augustine's implementation, this small-scale study sought to discover 'things' and 'signs,' both of which refer to symbols contained in the novel Khotbah di Atas Bukit. The descriptive qualitative method was used as the research design in order to achieve the research's goal. This study's data included words, sentences, and paragraphs from the novel's dialogues that represented 'things' and 'signs,' as previously stated. Khotbah di Atas Bukit Novel itself served as the data source. The area that has been analyzed by other researches was found in Islamic values and prophetic dimensions in the novel while the symbols (things and signs) as one types of figurative languages has become the aspect that has not been yet explored. The findings revealed that things to be used were discovered between the main character himself, namely Barman, who was more concerned with worldly materials, and Barman's anxiety in facing this life. Meanwhile, things to enjoy were described by Barman's opposite character, Humam. Humam's consistent association of the worlds with God's existence influenced Barman's perspective on life and attitude.